PEMAKNAAN SIMBOL MUTIARA DALAM NOVEL THE PEARL KARYA JOHN STEINBECK - NFN Karyono (SAWERIGADING, 2011)
This research is aimed to reveal the meaning in the novel 'The Pearl" through semiotic way. The method usedin this research is semiotic method which refers to the step meaning of basic narative, the meaning of pearlsymbol, community description, the e f f e c t of pearl existence toward the change of social status and the socialproblems in The Pearl. The meaning of pearl symbol in The Pearl reveals the features in a literature text byusing semitic approach. The analogy of pearl is as a valuable thing which is very expensive. This means thatpearl is very closed to wealth. The pearl in this novel is a very big pearl which is very expensive so that it iscalled pearl of world. Therefore, the pearl is a symbol of rules. AbstrakPenelitian ini untuk mengungkap makna yang terkandung dalam cerita The Pearl melalui kajiansemiotik. Metode yang digunakan adalah metode deskriptif kualitatif dengan mengacu padalangkah pemaknaan pada skema naratif dasar, pemaknaan simbol mutiara, gambaranmasyarakat, pengaruh eksistensi mutiara terhadap perubahan status sosial, dan masalahmasalahsosial dalam The Pearl. Pemaknaan simbol mutiara dtalam The Pearl karya John Steinbeck inimengungkapkan tentang tanda-tanda dalam suatu teks sastra dengan pendekatan semiotika.Pemaknaan mutiara merupakan sebuah benda berharga yang berharga mahal. Ini berartimutiara erat kaitannya dengan kekayaan. Mutiara yang ditampilkan dalam novel ini adalahmutiara yang sangat besar yang tak ternilai harganya sehingga di sebut mutiara dunia. Dengandemikian mutiara ini merupakan simbol kekuasaan.